Improving the outcomes of community forests in Suriname - Recommendations for CSOs - Kanten, R. van; Razab-Sekh. G. (2020)
As part of a multi-country review of community forest rights, Tropenbos Suriname conducted a review of the community forests in Suriname, to understand the extent to which they result in positive conservation and livelihood outcomes, and to identify the conditions for their success and ways in which Civil Society Organisations (CSOs) can help with achieving these. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.